TREATMENT OF Pangasionodon hypophthalmus INFECTED BY BACTERIA Edwarsiella tarda WITH SOLUTION OF APEL MANGO LEAF( Mangifera indica ) - Atika Talitha Erman; Henni Syawal; Iesje Lukistyowati (Berkala Perikanan Terubuk, 2021)
Apel Mango leaf is a natural ingredient that can be used as an alternative medicine because it has phytochemical content in the form of tannins, flavonoids, saponins and alkaloids. This study aims to analyze the effect of giving a solution of apel mango leaf (Mangifera Indica) in the treatment of Pangasionodon hypophthalmus, and get the best dose for the treatment of diseases caused by E. tarda bacteria, seen from total leukocytes , leukocyte differentiation, phagocytic activity and survival of Pangasionodon hypophthalmus. This study uses a completely randomized design (CRD) with 5 treatments and 3 replications. The dosage of apel mango leaf solution used was Kn (not infected and not treated) Kp (infected and not treated), P1 (1.2%), P2 (1.4%) and P3 (1.6%) . Immersion is carried out in 5 liters of water with a mixture of mango leaf solution in accordance with different doses for 5 minutes 3 times soaking interval of 2 days , then maintained for 14 days after treatment . The results showed that soaking with apel mango leaf solution significantly affected the image of leukocytes of P. hypophthalmus (P <0.05) . Best dose contained in treatment P2 (1.4%) with an average total leukocytes ( 8,33 × 104 cells / mm 3 ) , differentiation of leukocytes (lymphocytes 84.33%, monocytes 9,00 and 6,67 neutrophils %), phagocytic activity ( 36.00% ) and survival rate of Pangasionodon hypophthalmus ( 86.67% ) .